2015
DOI: 10.17794/rgn.2015.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Analiza konstrukcijskih i radnih veličina lančane sjekačice

Abstract: Učinkovit način eksploatacije blokova kamena ostvaruje se kombiniranjem lančane sjekačice i dijamantne žične pile zbog mogućnosti korištenja prednosti jednog ili drugog stroja. Lančane sjekačice se koriste za izradu horizontalnih i vertikalnih rezova, a primjenu su našle u površinskoj i podzemnoj eksploataciji u slabo do srednje abrazivnim i mekim do srednje tvrdim stijenama. Učinkovitost lančane sjekačice pri eksploataciji arhitektonskog kamena ovisi o pravilnom izboru radnih veličina stroja, reznih elemenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A very good correspondence of the speci c cutting energy tested in the laboratory on a linear cutting machine with the eld tests (chain saw) was proved and presented in the PhD thesis by Korman (2014). In other words, the linear cutting machine can be used to simulate the cutting process of the chain saw (Korman at al., 2015b).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…A very good correspondence of the speci c cutting energy tested in the laboratory on a linear cutting machine with the eld tests (chain saw) was proved and presented in the PhD thesis by Korman (2014). In other words, the linear cutting machine can be used to simulate the cutting process of the chain saw (Korman at al., 2015b).…”
Section: Introductionmentioning
confidence: 94%
“…A very similar measurement system was used by Korman when studying the in uence of construction and operating parameters on the ef cacy of the chain saw (Korman, 2014) and the in uence of the physical and mechanical characteristics of rocks on energy consumption of the jaw crusher during crushing (Korman et al, 2015a).…”
Section: Measuring System For Measuring Energy Of Cutting or Drillingmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained data points to the fact that certain chain constructions are more efficient than others in view of the specific energy and the tool wear. The in-situ tests have shown that in the case of using electrical hydraulic saws, the increase of the ratio between the cart speed and the chain speed increases the depth of the cut and reduces the specific cutting energy (Korman et al, 2015a). Hekimoglu (2014) concluded that the specific energy may be reduced by 45% if the length of the cutting sequence is doubled.…”
Section: Introductionmentioning
confidence: 99%